Ethnochemistry: Analysis of the Relevance of Material Atomic Structure with the Ngejot Tradition as a Source for Learning Chemistry - Nanda Suanda; Dwi Wahyudiati (Universitas Pendidikan Mandalika, 2023)
Limitations in the form of teaching materials as learning resources in chemistry learning is a problem that occurs quite seriously in secondary schools and in tertiary institutions so the ethnochemistry approach is one form of modification in the development of contextual chemistry teaching materials. This study aims to analyze chemistry teaching materials as a source of learning by exploring the potential of local Sasak wisdom with the ngejot tradition. Data collection techniques through literature, interviews, and documentation using a qualitative approach. The use of Miles & Huberman's qualitative analysis in analyzing the data to be obtained. The research subjects consist of community leaders, chemical content experts, and chemical literature relevant to the research study. Based on the research findings, it can be concluded that Sasak local wisdom with the ngejot tradition can be used as a source of chemistry learning through integrating Sasak local wisdom with the ngejot practice in the concept of atomic structure that there is an arrangement of matter from a negatively charged electron surrounding the atomic nucleus. Thus, the implications of this research can be a source of reference in developing contextual chemistry teaching materials so as to make learning more meaningful.